Analisis Kesulitan Belajar Siswa Kelas IV Sekolah Dasar Pada Materi Bangun Datar Dan Bangun Ruang - Alisia Rahmadini; Jesi Alexander Alim (Guruku: Jurnal Pendidikan dan Sosial Humaniora, 2023)
Mathematics is one of the sciences that plays an important role in various aspects of human life. One of the materials in mathematics is geometry which includes flat and spatial shapes. Based on the facts in the field, it is found that students have learning difficulties in the material of flat and spatial shapes. This research aims to analyze the learning difficulties of grade IV elementary school students on flat and spatial shapes in learning with the independent curriculum along with the causes and solutions to these problems. This research uses a qualitative method with an exploratory descriptive approach. The data sources in this study came from observations, interviews, and literature studies. The subjects of this research were 10 fourth grade students of SD Negeri 183 Pekanbaru and SD Guang Ming 1 Pekanbaru. The results showed that there were still difficulties felt by fourth grade elementary school students in learning mathematics with the independent curriculum, especially in the material of flat and spatial shapes. It does not rule out the possibility of misconceptions or incomplete understanding of concepts in the material of flat and spatial shapes in grade IV elementary schools both public and private. The solution to this problem is to apply appropriate and interesting concrete learning media and improve the quality of teaching material by educators in teaching the concept of flat and spatial building material thoroughly and accurately.